Optimized green extraction conditions of matcha green tea (Camellia sinensis) using central composite design for maximal polyphenol and antioxidant contents - Sayuti, Nor Hafiza; Kamarudin, Ammar Akram; Saad, Norazalina; Ab Razak, Nor Asma; Mohd Esa, Norhaizan (North Carolina State University * College of Natural Resources, 2021)
Response surface methodology (RSM) was employed to optimize the extraction conditions of phenolic and antioxidant compounds from matcha green tea (Camellia sinensis) using central composite design (CCD). The desirability function was used to find the optimum extraction conditions. The highest polyphenol and antioxidant content yield were reached at a temperature of 80 °C, an extraction time of 20 min, a liquid-to-solid ratio of 100 mL/g, and a desirability value of 0.948. The experimental values for total phenolics under the optimum extraction conditions were 317.62 ± 3.45 mg GAE/g and 29.21 ± 0.38 mg RE/g for the total flavonoids. The antioxidant activity (AA) was evaluated using 2,2 diphenyl-1-picrylhydrazyl (DPPH) and 2,2-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), which showed radical scavenging activities at 88.28 ± 0.14% and 90.02 ± 0.14%, respectively. The high performance liquid chromatography (HPLC) analysis at the optimum condition revealed 14 compounds. Among the analyzed compounds, matcha green tea extract (MGTE) had the highest content of epigallocatechin gallate (EGCG) with 95.48 mg/g, followed by epicatechin gallate (ECG) at 74.48 mg/g, and catechin at 28.94 mg/g. The results suggested that the optimized parameters of heat-assisted extraction provide an ideal green extraction method for the extraction of the high polyphenol and antioxidant content in matcha green tea.